Let us play: (un)shackling liaisons, (un)masking games and (un)hindered dialogue in the arena where theology takes place - Van Wyk, Tanya ca. 20./21. Jh. (Verbum et ecclesia, 2017)
This contribution is a political-theological and hermeneutical reflection on the origin, nature, intention and contribution of a research theme identified within the dynamics of an institutional space, by taking a critical look at the rules' and the game' of university academia. Specific reference is made to institutional and faculty research themes, namely reconciling diversity' and Ecodomy - life in its fullness'. The institutional academic space is compared to a Hunger Games-style panopticon, with its rules' and play'. It is argued that these research themes can only make an authentic contribution if the play' and game'of the space in which these themes originate, are deconstructed. If this deconstruction can take place, there might be an authentic chance for unhindered dialogue towards the transformation of the academic space and the greater community it serves.